1988
DOI: 10.1007/bf01726924
|View full text |Cite
|
Sign up to set email alerts
|

Non-responsiveness to hepatitis-B vaccination: Revaccination and immunogenetic typing

Abstract: Summary. The variation in immune responses to standard inoculation of the hepatitis-B virus vaccine suggest that host factors influence response in ways that are not presently understood. We studied 25 low/nonresponding health care workers (anti-HBs titer < 50 IU/1) after the third inoculation of an experimental hepatitis-B vaccine to determine their immune status (through lymphocyte phenotypes) and HLA type. After application of a fourth inoculation, the seroconverting subjects showed only low anti-HBs levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…This association was confirmed in healthy persons by Craven et al [5] but was not observed in further studies [4,7,8]. The strongest association with a low humoral immune response to hepatitis B vaccine was found with the DR3 aUele in healthy persons [2][3][4]6] and in haemodialysis patients [7,8]. The differences between responders and non-responders in the incidence of this allele, however, were markedly lower in the previous studies as compared to our present work.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This association was confirmed in healthy persons by Craven et al [5] but was not observed in further studies [4,7,8]. The strongest association with a low humoral immune response to hepatitis B vaccine was found with the DR3 aUele in healthy persons [2][3][4]6] and in haemodialysis patients [7,8]. The differences between responders and non-responders in the incidence of this allele, however, were markedly lower in the previous studies as compared to our present work.…”
Section: Discussionsupporting
confidence: 77%
“…Some data on the influence of the presence or association between HLA aUeles and the immune response to absence of certain MHC class I, II and III aUeles on the hepatitis B immunization. These studies were performed either in healthy persons [2][3][4][5][6] or in end-stage renal disease (ESRD) patients [4,7,8]. The risk of acquiring hepatitis B infection of these patients is high especially following haemodialysis treatment, therefore immunization with hepatitis B vaccine is highly recommended.…”
Section: Judit Kramer Phd National Institute Of Haematology Blood Tmentioning
confidence: 99%
“…transforming growth factor-[, leukotrienes, prostaglandins-E, TNF-00 may suppress antigen-induced T lymphocyte proliferation. 31,2,6 Using flow cytometry methods, quantitative determination of monocyte phagocytosis was possible.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these impediments, we have recently demonstrated that the human antibody response to immunization with the HBsAg vaccine is MHC associated. Many clinical studies have demonstrated that up to 7.5% of otherwise healthy HBsAg vaccine recipients are poor or nonresponders (5)(6)(7)(8)(9)(10)(11). In our initial study of a group of such nonresponders, we noted an increased incidence of individuals presumably homozygous (by phenotype) for the HLA class I gene HLA-B8, the class II gene HLA-DIL3, and the genes for the complement proteins BF*S, C2"C, C4A*QO (a null gene), and C4B'1 (12).…”
mentioning
confidence: 99%